CBMT-15. MET INHIBITION DRIVES PGC1A DEPENDENT METABOLIC REPROGRAMMING AND ELICITS UNIQUE METABOLIC VULNERABILITIES IN GLIOBLASTOMA. (11th November 2019) - Zhang, Yiru; Nguyen, Trang; Zhao, Junfei; Shang, Enyuan; Torrini, Consuelo; Canoll, Peter D; Karpel-Massler, Georg; Siegelin, Markus
Abstract: The receptor kinase, c-MET, has emerged as a target for glioblastoma therapy. However, treatment resistance evolves inevitably. By performing a global metabolite screen with metabolite set enrichment coupled with transcriptome and gene set enrichment analysis and proteomic screening, we have identified substantial reprogramming of tumor metabolism, involving oxidative phosphorylation and fatty acid oxidation (FAO) with a substantial accumulation of acyl-carnitines accompanied by an increase of PGC1a in response to genetic (shRNA and CRISPR/Cas9) and pharmacological (crizotinib) inhibition of c-MET. Extracellular flux and carbon tracing analyses (U- 13 C-Glucose and U- 13 C-Glutamine) demonstrated enhanced oxidative metabolism, which was driven by FAO and supported by increased anaplerosis of glucose carbons. These findings were observed in concert with increased number and fusion of mitochondria and production of reactive oxygen species (ROS). Genetic interference with PGC1a rescued this oxidative phenotype driven by c-MET inhibition. Silencing and chromatin immunoprecipitation experiments demonstrated that CREB regulates the expression of PGC1a in the context of c-MET inhibition. Interference with both oxidative phosphorylation (metformin, oligomycin) and beta-oxidation of fatty acids (etomoxir) enhanced the anti-tumor efficacy of c-MET inhibition. Moreover, based on a high-throughput drug screen, we show that gamitrinib along with c-MET inhibition results in synergistic cell death. Finally, utilizing patient-derived xenograft models, we provide evidence that the combination treatments (crizotinib+etomoxir and crizotinib+gamitrinib) were significantly more efficacious than single treatment without induction of toxicity. Collectively, we have unraveled the mechanistic underpinnings of c-MET inhibitor treatment and identified novel combination therapies that may enhance the therapeutic efficacy of c-MET inhibition.